Avaliação do condicionamento osmótico para aplicação de micronutrientes em sementes de soja - Colognese, Izabella Chrispim (2020)
The objective of this experiment was to evaluate the effect of zinc and boron treatment associated with osmoconditioning, on the physiological quality of soybean seeds with different levels of vigor. The work was carried out at the Didactic Laboratory of Seed Analysis, of the Federal Technological University of Paraná, Campus Pato Branco, in a completely randomized design. Batches of soybean seeds of cultivar TMG 7262® with three levels of vigor (very high, high and medium) were used, submitted to eight associations of seed treatment (TS) with zinc and boron and osmoconditioning: T1 = control; T2 = osmoconditioning + without TS; T3 = osmoc. + TS boron; T4 = osmoc. + TS zinc; T5 = TS boron + TS zinc; T6 = osmoc. + TS boron + TS zinc; T7 = TS boron and T8 = TS zinc. For the TS, the commercial products Ager Boro® (46 mL / 100 kg-1 of seeds) and Maxi Zinc® (87.5 mL / 100 kg-1 of seeds) were used. For osmoconditioning, the seeds were placed in a gerbox, under a sheet of blotting paper moistened with 10 mL of PEG 6000 + Vitavax Thiran 200 SC solution (0.2%), with an osmotic potential of -0.2 MPa. The seeds were taken to a BOD, at 20º C for 96 hours and afterwards, they were washed in running water and submitted to drying for 48 hours at 20º C. The evaluation of the physiological quality was carried out using the germination tests (GERM), accelerated aging (EA), emergency speed index (IVE), emergency speed (VE), electrical conductivity (COND), shoot length (CPA) and root (CPR), shoot green mass (MVPA) and root (MVR), shoot dry mass (MSPA) and root (MSR) and field emergence (EC). The data of the variable IVE were transformed using the formula √(Yijk+0,5) and all the data of the experiment were submitted ANOVA (5%), where the means with significant differences were grouped by the Skott-Knott test (5%), through the Genes software. It was concluded that the treatment of seeds with zinc increases the vigor of soybean seeds, regardless of the initial vigor level, however, the treatment with boron results in a decrease of vigor, for all levels of studied. In addition, the osmoconditioning of seeds if performed in isolation, does not cause increases in physiological quality, but if associated with the treatment of seeds with zinc and boron, it presents a significant increase in the physiological quality of seeds.